Zakat Institutions and Management: A Comparison of Zakat Models, Types, and Arrangements in Middle Eastern Countries and Indonesia - Haseena Khalida Faaza; Franciskus Antonius Alijoyo (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study aims to understand the relationship between human factors, ethical leadership, and a risk-aware culture in underwriting practices in the general insurance industry in Indonesia. The study uses a descriptive qualitative approach with secondary data sources derived from previous research, insurance industry reports, and articles from national and international mass media. Analysis is conducted using a thematic approach by examining narratives and patterns of relationships between concepts. The results show that the quality of human resources and ethical leadership are key to establishing an effective risk-aware culture. These findings emphasize the importance of risk governance oriented towards ethical behavior and organizational learning in the general insurance sector in Indonesia.